The importance of loco-regional control in metastatic rectal cancer - Martini, Stefania; Iorio, Giuseppe Carlo; Arcadipane, Francesca; Ricardi, Umberto; Franco, Pierfrancesco (Therapeutic Radiology and Oncology, 2019)
The number of new cases of rectal cancer (RC) estimated per year is across 704,000 worldwide. Approximately 310,000 death cases are reported per year among RC patients, globally (1). Roughly 20% of patients with RC present with metastatic disease and their prognosis depends on the extent of tumor burden (2).